Exploitation of food-plants in the Early and Middle Holocene Blue Nile area, Sudan and neighbouring areas Explotación de plantas comestibles durante el Holoceno Inicial y Medio en el área del Nilo Azul, Sudán - A-magid, Anwar (Complutum, 2003)
Plant impressions were found on pottery from two Early Holocene (Early Khartoum) sites and one Middle Holocene (Shaheinab) site in the Blue Nile area in the Central Sudan. Identification of the specimens attests the presence of edible plants and other plant species. Analysis of the data indicates that a broad-spectrum subsistence strategies including exploitation of grain-foods (e.g. wild cereals and grasses) was initiated during the Early Holocene (2000 years earlier than previously thought) and continued to be practised during the Middle Holocene without significant change. These strategies were part of a general pattern of food-plants exploitation in the wider area of Northeast Africa during the Early and Middle Holocene. Although no direct evidence of cultivation was found, the possibility of its being practised is not excluded. Some of the recovered evidence indicates that climatic conditions were much wetter than today. An attempt is made to emphasise why and suggest how archaeobotanical research can be manipulated to help solving certain cultural and socio-economic problems in modern times.